Sistem Monitoring Tumbuh Kembang Anak Berbasis Web Menggunakan Metode Rapid Application Development : Studi Kasus: UPT Puskesmas Medan Johor - Syifaa Salsabiila Putri; Ahmad Zakir; Andi Marwan Elhanafi (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
Posyandu services as part of community -based health efforts still face challenges in data management in posyandu activities that are mostly carried out manually, such as recording toddler data, immunization schedules, and monthly reports that result in data irregularities, information duplication, and delays in services. This has an impact on time efficiency, accuracy of recording, and difficulties in reporting and monitoring children's growth and development. This study aims to develop a web -based health monitoring monitoring system and growth and development of children at the Medan Johor Puskesmas UPT. The importance of this research is based on the need for information systems that are efficient, accurate, and can be accessed in real-time by Posyandu cadres, heads of puskesmas, and parents of toddlers. The main objective of this study is to design and implement a web -based system that can help the registration process, growth and development, as well as digital recording of immunization. This study uses the Rapid Application Development system development method because it is fast, iterative, and greatly involves users in the development process. The results of this study indicate that the system that was built can increase cadre working time efficiency, reduce the risk of data loss, and facilitate access to information for parents.